Value Conservatism and its Challenge to Consequentialism. Issue 3 (September 2021) - Sass, Reuben
Abstract: G. A. Cohen's value conservatism entails that we ought to preserve some existing sources of value in lieu of more valuable replacements, thereby repudiating maximizing consequentialism. Cohen motivates value conservatism through illustrative cases. The consequentialist, however, can explain many Cohen-style cases by taking extrinsic properties, such as historical significance, to be sources of final value. Nevertheless, it may be intuitive that there's stronger reason to preserve than to promote certain sources of value, especially historically significant things. This motivates an argument that the weights of our reasons to preserve such things are especially strong relative to the amounts of value they bear. The value conservative can then explain these intuitions in non-consequentialist terms. There may be reason to preserve historically significant things as a matter of recognition respect for a cultural and historical heritage, or because it is virtuous to cultivate the right kind of connection with such a heritage.